2014
DOI: 10.1371/journal.pone.0108055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Study on Magnetic Iron Oxide Nanoparticles for MRI Tracking of Adipose Tissue-Derived Progenitor Cells

Abstract: Magnetic resonance imaging (MRI) using measurement of the transverse relaxation time (R2*) is to be considered as a promising approach for cell tracking experiments to evaluate the fate of transplanted progenitor cells and develop successful cell therapies for tissue engineering. While the relationship between core composition of nanoparticles and their MRI properties is well studied, little is known about possible effects on progenitor cells. This in vitro study aims at comparing two magnetic iron oxide nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
1
29
1
Order By: Relevance
“…On the contrary, other groups have demonstrated that SPIO nanoparticles have little toxicity and few side effects on cell activity and proliferation (Suh et al, 2009;Crabbe et al, 2010). A recent study revealed that improved MRI properties of multi-core nanoparticles may result in altered cell functions (Kasten et al, 2014). In addition, an inhibitory effect of SPIO nanoparticles on MSCs differentiation and signaling mechanisms has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other groups have demonstrated that SPIO nanoparticles have little toxicity and few side effects on cell activity and proliferation (Suh et al, 2009;Crabbe et al, 2010). A recent study revealed that improved MRI properties of multi-core nanoparticles may result in altered cell functions (Kasten et al, 2014). In addition, an inhibitory effect of SPIO nanoparticles on MSCs differentiation and signaling mechanisms has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…As a rule, in vitro cytotoxicity tests are conducted using exposure times up to 24 h. Furthermore, the long-term tests are not common with NPs, even though long-term cytotoxicity tests are not rare (Wagner et al 2009;Kasten et al 2014;Müller et al 2007). It has been discussed that there could be a linear correlation between short and long-term toxicity (Scheers et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the influence of IONPs exposition and their intracellular accumulation on the functional capabilities of hASCs is still incomplete and partially controversial [14,43,44]. Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45].…”
Section: Discussionmentioning
confidence: 71%
“…Stroh et al, who used the same concentration of the same IONPs, also found no effect on the cell viability of haNSCs and murine embryonic stem cells (mESC) 8 h and 48 h after the labelling procedure [3]. Some authors describe a concentration-dependent impairment of the viability of ASCs, BMSCs and other cell types after labelling or exposure to IONPs [3,15,47,48], which is thought to be mediated by various cellular changes such as oxidative stress [3,15,42,44,47,49].…”
Section: Discussionmentioning
confidence: 99%